Designing the Chinese post-Imperial capitals in correspondence of political chances: A comparative analysis of planning proposals for Nanjing in the thirties and Beijing in the fifties - Bona, Domenica (International Planning History Society Proceedings, 2018)
With a historical and morphological approach, this paper marks the correlation between the critical junctures occurred in China from 1911 to 1958 and the new planning proposals for the modern capital cities rebuilt at that time, Nanjing and Beijing. This paper assumes that the modern breaking points of Chinese history have the key role in reshaping the urban landscape as in the past. From this perspective, the research assumes an ‘interpretative morphological approach’ based on the comparison of the case studies. Stressing the attention on the planning features of each proposal, it is possible to highlight, firstly, the way new plans reproduce the classic patterns and override them in accordance with the political ideals and propaganda meanings that architecture and urbanism are supposed to embody; secondly, a constant application of traditional forms and urban patterns, by citation and reinterpretation. These two orders of results could eventually prove that reactionary and revolutionary political forces are influenced by the same atavistic rhetorical frameworks when they come to draw the spatial palimpsest of their power. Thus, each critical juncture is a new testing ground for the resistance of those recurring planning features in the present days as in the past.